Metacognitive Strategies of English Department Students in Virtual Speaking Assessment - Christina Waso Odung (Beyond Words, 2022)
Metacognitive strategies are learners’ strategies to think or organize their learning. There have been a lot of studies conducted on this subject area in which most of them quantitatively found that there were differences in the frequency of using metacognitive strategies between different achievers. This study is specially presented to depict how students deploy their metacognitive strategies especially in facing and executing a language assessment, performing a persuasive speech virtually. The l assessment should be conducted virtually in an English Education study program in Indonesia due to the Covid-19 outbreak. There were 11 participants from a speaking class of the department from different level of achievements took part in the study. The high, middle, and low achiever joined a stimulated recall interview to pour everything in their mind when they were preparing for the persuasive speech assessment, executing it, and evaluating it.  Based on the investigation done through stimulated recall interview, the study reveals that there are differences between high, middle, and low achievers in preparing for the final test and in executing it, in which the high performer achievers prepared more comprehensively in the preparation which affect to their performance. The study also confirms that higher achievers have more responsibilities and confidence compared to the low achievers in preparing for their task performances.